2020
DOI: 10.1111/jcpe.13333
|View full text |Cite
|
Sign up to set email alerts
|

Gingival inflammation influences oral health‐related quality of life in individuals living in a rural area of southern Brazil

Abstract: AimThe aim of the present cross‐sectional study was to evaluate whether the extent levels of gingival inflammation (GI) in whole mouth or restricted to the anterior region are independently associated with oral health‐related quality of life (OHRQoL) in individuals living in a rural area of southern Brazil.Materials and methodsA probability sample of 688 individuals was submitted to a full‐mouth periodontal examination at six sites on each tooth. Extent levels of GI in whole mouth and restricted to anterior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the researches of Oliveira et al, (2020) titled "Gingival inflammation influences oral healthrelated quality of life in individuals living in a rural area of southern Brazil ", it was concluded that with more care of child mouth, health could provide interdisciplinary cares for children in their life. In the researches of Parish et al, (2018) titled "intimate screening of children in dentistry environment", it was concluded that making central IPV interferences in dentistry training and making cooperation in relation with general attitude change to the trend of tooth treatment helps to simplify IPV screening in dentistry environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the researches of Oliveira et al, (2020) titled "Gingival inflammation influences oral healthrelated quality of life in individuals living in a rural area of southern Brazil ", it was concluded that with more care of child mouth, health could provide interdisciplinary cares for children in their life. In the researches of Parish et al, (2018) titled "intimate screening of children in dentistry environment", it was concluded that making central IPV interferences in dentistry training and making cooperation in relation with general attitude change to the trend of tooth treatment helps to simplify IPV screening in dentistry environment.…”
Section: Introductionmentioning
confidence: 99%